Ileoanal pouch for the treatment of adenomatous polyposis and ulcerative colitis--clinical and functional results. - Leite, J F (1992)
The results of the first 9 patients with proctocolectomy and ileal pouch operated on between 1983 and 1990 were analysed. This procedure was carried out in 8 patients with adenomatous polyposis. Three of these patients had an associated rectal cancer and one a degenerated sigmoid polyp. One patient had ulcerative colitis and was previously submitted to a colectomy related with perforated fulminant colitis. Three types of pouches were constructed: 3 S, 3 J and 3W, all with a temporary ileostomy. A circular stapler was used in 2 cases for ileoanal anastomosis. Three postoperative complications were observed: two patients with pouchitis during the presence of a diverting ileostomy and an ileal fistula following ileostomy closure, all medically treated. Clinical and functional results were evaluated 1 to 7 years after the procedure. The average daytime stool frequency was 4 with 1 nocturnal. All patients indicated normal continence. One patient had her professional life affected due to the increased number of defecations. Differences in the clinical results of the patients with S, J and W pouches were not statistically different. The functional results expressed as median and range were as follows: resting and pressure 45 cm H2O (20-60), voluntary anal pressure 70 cm H2O (34-120), compliance 3.70 ml/cm H2O (1.14-11.40), maximal tolerated volume (MTV) 320 ml (110-48) and threshold volume 95 ml (40-170). The MTV values of the groups with J and W pouches were 190 ml (180-200) and 370 ml (340-480), respectively (p = 0.05).(ABSTRACT TRUNCATED AT 250 WORDS)